Pemanfaatan Sari Timun untuk Mengurangi Tingkat Stres dan Meningkatkan Kelangsungan Hidup Pascalarva Udang Vaname (Litopenaeus vannamei) selama Masa Penurunan Salinitas - Ferdinand Hukama Taqwa; Marsi Marsi; S. Haris (Research Center for Suboptimal Lands (PUR-PLSO), Universitas Sriwijaya, 2016)
Taqwa et al, 2016.Â The Using of Cucumbar Extract to Reduce the Stress Level and Increase the Survival Rate of White Shrimp Postlarvae (Litopenaeus vannamei) during Salinity Decreasing Time. JLSO 5(1):53-61.The purpose of this study was to evaluate the effect of adding cucumber extract on the level of stress and survival of white shrimp postlarvae during acclimatization. The method used was completely randomized design with five treatment and three replication of adding cucumber extract that equal 15 ppm (T1), 30 ppm (T2), 45 ppm (T3), 60 ppm (T4) and without adding cucumber extract (T0) as a control. The results showed that addition of cucumber extract equivalent to 15 ppm (T1) in diluents media during 96 hours of acclimatization produce survival 91.67%, body fluid glucose levels are lower at 161.67 mg dl-1 and consumption level of oxygen 4.39 mg O2 g-1 h-1. Physical chemistry value of media acclimatization still in tolerance except in ammonia